33.7k views
1 vote
I dont get this Rewrite the equation below so that it does not have fractions. 2-(3)/(4)x=(9)/(10) Do not use decimals in your answer.

User Amareswar
by
5.5k points

1 Answer

4 votes

Answer:

Suppose we have an equation like:


(A)/(C) = (B)/(D)

If we want to remove the denominators, we should multiply both sides by each denominator.

First, let's multiply both sides by C.


(A)/(C)*C = (B)/(D)*C


A = (B)/(D)*C

Now let's multiply both sides by D.


A*D = (B)/(D)*C*D


A*D = B*C

So now we removed the denominators.

Now let's do this to our expression.


2 - (3)/(4*x) = (9)/(10)

First, let's multiply both sides by 10


(2 - (3)/(4*x))*10 = (9)/(10)*10


20 + (30)/(4*x) = 9

Now let's multiply both sides by 4*x


(20 + (30)/(4*x))*4*x = 9*4*x


20*4*x - 30 = 9*4*x


80*x - 30 = 36*x

Now we can solve this for x:


80*x - 36*x = 30


44*x = 30


x = (30)/(44) = 0.68

User Cengiz Sevimli
by
5.5k points